Об антропологии, этнографии и обсуждении работ Тима Ингольда - Функ, Дмитрий Анатольевич 1962- (Сибирские исторические исследования)
Рец. на : Ahmad, Irfan (ed.) Anthropology and Ethnography Are Not Equivalent. Reorienting Anthropology for the Future. New York: Berghahn, 2021. xi, 160 p. (Methodology and History in Anthropology, vol. 41) ISBN 9781789209891 (ebook)